A realistic solution of overcoming disadvantage of Compton suppression spectrometer. (June 2019) - Zhang, Weihua; Lam, Kenneth; Liu, Chuanlei
Abstract: To achieve low detection limits for radionuclide analysis, Compton continuum suppression gamma-ray spectrometer has been used for several decades. The most serious disadvantage arises when radionuclides measured have cascade gamma emissions. This is a major limitation of the technique in environmental sample analysis. The digital list-mode data acquisition techniques in conjunction with time stamped pulse analysis method presented in this paper recovers the undesired full-energy-peak (FEP) coincidence losses for cascade radionuclides while retains suppression of true Compton events to keep the improved detection limit, thus extending the usefulness of the anti-Compton spectroscopy. In this study, software are developed to analyse the radionuclides with a relative simple decay scheme, such as 22 Na, 60 Co and 88 Y, and a complex decay scheme, such as 125S b, 134 Cs, 152 Eu and 154 Eu. The results indicated that in the reconstruct anticoincidence spectra the FEP restoration efficiency, both for minor and major peaks, is near 100%. Highlights: A digital list-mode data acquisition Compton suppression spectrometer was developed. Software made to recover the full-energy (FEP) peak losses in the spectrometer. Radionuclides with complex and simple decay schemes were analysed with the software. The FEP restoration efficiency, both for minor and major peaks, is near 100%.